Multicriteria Evaluation-GIS Integration Framework for Landfill Site Selection in Limited Space Regions: A Case Study in the West Bank - Ayah H. Helal (Advances in Civil Engineering)
Unplanned solid waste disposal is a global challenge that has created severe environmental and health problems, especially in developing countries. The West Bank, a developing region in the Middle East, is an example of a limited space region that suffers dangerous pollution, hazardous odors, and contaminated plantations as consequences of unplanned solid waste dumping sites and landfills. Limited space allotted to the West Bank Palestinians, making it highly inhabited, is the main reason behind the current allocation of solid waste dumping sites that are close to the residential area. Multicriteria evaluation (MCE) method, integrated with geographic information system (GIS) software, is employed here to find optimal solid waste disposal locations in the West Bank. The model assumes the input of two-factor types, namely natural and artificial. These two types include nineteen criteria. Based on the MCE method, a hierarchy criteria scheme has been developed and used in data analysis by GIS. The hierarchy scheme divides each required criterion into subcriteria with rankings to be presented. Each criterion has been weighted and intersected by the weight overlaying process in GIS to provide the most suitable locations for regional landfills inside the West Bank. Each existing landfill location has then been examined for compliance with the criteria. The results show that all regional five landfills, including a future planned site, exist in the restricted area determined here. However, one landfill is close to suitable places and can be relocated easily. Moreover, about 323.57 km2 can be sufficiently used for regional landfills inside the West Bank, mostly available in the Eastern parts. The findings confirm the applicability of the MCE-GIS integration strategy in future planning of landfill siting in areas of limited space.